PENGARUH FASILITAS SISTEM PELACAKAN ONLINE, KETEPATAN WAKTU PENGIRIMAN, HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN J&T EXPRESS (Studi Pada J&T Express Cabang Kota Karanganyar) - Oktaviana Dwi Mawarni; Suyatmin Waskito Adi (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
In the current era of globalization, shipping service companies have experienced a rapid increase. This is caused by several factors, one of which is the increasing interest in shopping through electronic markets or commonly referred to as e-commerce. Therefore, this study aims to find empirical evidence of the effect of online tracking system facilities, on time delivery, price, and service quality on customer satisfaction. The population referred to in this study are customers who use the services of J&T Express Karanganyar. The sample in this study used 100 respondents who were customers or service users of J&T Express Karanganyar. The data analysis method uses multiple linear regression analysis with the help of SPSS 21 software. The results of the study found that on time delivery and service quality affect customer satisfaction J&T Express Karanganyar with a sig value. respectively (0.001 < 0.05) and (0.008 < 0.05). Meanwhile, online tracking system facilities and prices have no effect on J&T Express Karanganyar customer satisfaction with a sig value. respectively (0.393 > 0.05) and (0.653 > 0.05).